Delay‐aware and cost‐efficient probabilistic transmission for opportunistic networks. Issue 6 (3rd November 2020) - Li, Jun; He, Xing‐Yu; Zhao, Dan; Yang, Gui‐Song; He, Dao‐Jing; Chan, Sammy
Abstract : The opportunistic network has become an appealing paradigm since it can reduce the energy consumption and cost on cellular network connections and relieve the communication burden of cellular networks. The probabilistic transmission scheme has been proposed as one of the typical opportunistic transmission schemes. However, most existing probabilistic transmission schemes neglect that, opportunistic transmission tasks in some applications have transmission time and cost budgets, and to set proper delay and hop count thresholds on encountering probabilities between relay nodes and their destination nodes can help to filter redundant long‐delay and high‐cost opportunistic paths for packets. In this study, the authors proposed a delay‐aware and cost‐efficient probabilistic transmission method for opportunistic networks. In this method, direct and indirect encountering probabilities related to delay and hop count are defined, and accordingly, a relay node selection algorithm is provided with preset encountering delay and hop count thresholds to compare probabilities of nodes to encounter the destination node within the preset thresholds as their transmission quality metrics. The simulation results verify that the proposed method can reduce transmission delay and cost efficiently.